(untitled) (Eurasian Journal of Ecology, 2016)
The article provides a comprehensive evaluation of the biological state of Alakol lakes’ benthic fauna in the period between 2009 and 20U. The mean results obtained are comparable in all the lakes due to the similarities in taxonomic and quantitative characteristics of the zoobenthos. The range of values obtained corresponds to the low well-being of benthocoenosis.